Hubungan Pengetahuan, Frekuensi Menyusui Dan Hisapan Bayi Dengan Produksi ASI - Anjelina Puspita Sari; Romlah Romlah (Citra Delima Scientific journal of Citra Internasional Institute, 2022)
The coverage of exclusive breastfeeding is still below the target of achieving 80% both in the world and in Indonesia. This study aims to determine the relationship between knowledge, frequency of breastfeeding, and infant sucking with breast milk production. Methods: This type of research is observational analytic using a cross sectional design. The population in this study were all breastfeeding mothers with exclusive breastfeeding and PASI in the working area of ​​the 23 Ilir Health Center Palembang. The number of samples in this study was 85 respondents, the data was taken by distributing questionnaires. The sampling technique is purposive sampling. The data analysis technique used the Chi-Square test. Results: The results of statistical tests showed that there was a significant relationship between mother's knowledge and breast milk production (P=0.012), there was a significant relationship between breastfeeding frequency and breast milk production (P=0.006), and there was a significant relationship between infant sucking and breast milk production (P= 0.094). The conclusion in this study is that mothers need to have knowledge about the benefits of breastfeeding, so that mothers will often breastfeed their babies, the more often they are breastfed, the more milk production will be. Suggestions for health workers to continue to provide IEC regarding exclusive breastfeeding, especially for mothers who have no experience in breastfeeding.